2007
DOI: 10.1080/00016480601126986
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic and spinal pathology in the acoustic cortex in Alzheimer's disease: morphological and morphometric estimation by Golgi technique and electron microscopy

Abstract: The morphological and morphometric estimation of the acoustic cortex revealed loss of Cajal-Retzius cells in layer I, as well as an impressive abbreviation of the dendritic fields associated with loss of dendritic spines in all layers of the cortex. Numerous distorted, dystrophic and degenerated dendritic spines were also seen, which were intermixed with a considerable number of giant spines. The dendritic and spinal alterations were closely associated with mitochondrial alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
1
33
0
3
Order By: Relevance
“…Since memory and learning are associated with synaptic remodeling, oxidative modification and subsequent loss of function of this protein could conceivably be involved in the observed cognitive impairments in MCI and AD (74,107,260). Moreover, the decreased function of CRMP2 could be responsible for shortened dendritic length and synapse loss observed in AD (28,107). Shortened dendritic length would likely lead to less neuronal communication with adjacent neurons that could contribute to memory loss and cognitive decline associated with AD.…”
Section: Identification Of Carbonylated Proteins In Brainmentioning
confidence: 99%
“…Since memory and learning are associated with synaptic remodeling, oxidative modification and subsequent loss of function of this protein could conceivably be involved in the observed cognitive impairments in MCI and AD (74,107,260). Moreover, the decreased function of CRMP2 could be responsible for shortened dendritic length and synapse loss observed in AD (28,107). Shortened dendritic length would likely lead to less neuronal communication with adjacent neurons that could contribute to memory loss and cognitive decline associated with AD.…”
Section: Identification Of Carbonylated Proteins In Brainmentioning
confidence: 99%
“…In previous studies we have shown a correlation between morphological and spinal alterations of neurons and oxidative damage in degenerative diseases [4,5]. This could hold true for normal ageing too, while in the ageing brain there is a decline in the normal antioxidant defence mechanisms, which increase the vulnerability of the brain to the deleterious effects of oxidative damage [8].…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscope studies demonstrated a cor relation between oxidative stress and neuronal mor phological alterations [4].…”
Section: Age-related Changesmentioning
confidence: 99%
“…Cell soma of a corticotectal pyramidal neuron from an older brain [4] exhibiting significant loss of basal dendritic branches and dendritic spines (Golgi method, magnification 400×). Reconstruction from a corticocortical neuron from a younger brain [6].…”
Section: Quantitative Changesmentioning
confidence: 99%